Dynamic fragmentation of rock material: Characteristic size, fragment distribution and pulverization law. (August 2018) - Li, X.F.; Li, H.B.; Zhang, Q.B.; Jiang, J.L.; Zhao, J.
Highlights: Mechanical class I and class II are existed in dynamic stress vs. strain relations. Identifications of transition strain rate are discussed. Fragmentation patterns transits from splitting to pulverization with respect to strain rate. Build a fragment model considering the multi-dimensional breakage to study the dynamic fragmentation. Abstract: In this study, the dynamic fragmentation of granites at strain rates of 40–150/s is explored by using SHPB apparatus. Two mechanical classes (i.e. class I and class II) are observed from the stress vs. strain curves in high strain rate loading and the transition strain rate separated the two regimes is about 80/s. The samples are pervasively shattered when the strain rate exceeds the transition threshold and the dissipated energy density is as high as 2.0 J/cm 3 . Fragment size/mass distributions are quantified using image processing technique and Weibull distribution, which provide better agreements with experimental results. Then a novel energy-based fragmentation model for describing the cylindrical samples compacted by single direction impact is proposed to reasonably predict the characteristic fragment size. The compression kinetic energy item explains the catastrophic fracturing, which is a result of multi-dimensional breakage at high strain rate. The class I loading, described as 'strain energy controlled regime', produces larger-size, less-number debris and behaved as strain rate independent. The class II loading is kinetic energy controlled which results in pulverized debris and rate dependent failure strength.